The Relationships between Learning Organization Dimensions and Performance Among Malaysian Private Institutions of Higher Learning - Kumar, Naresh (2005)
Undoubtedly, today private colleges are mounting their effort to become a learning organization, which is believed to be the only solution to adapt to the new era. Indeed private enterprises have demonstrated how a learning organization can improve business performance. Thus, it seems reasonable for private higher learning institutions to apply the learning organization constructs to improve their institutional performance. Although the links between learning organization constructs and business performances have often been assumed, there are little empirical evidence to support this standpoint. Thus, this study was initiated to examine the relationships between learning organization dimensions, institutional characteristics and two perceived performance improvement measures, namely financial performance and knowledge performance among Malaysian private institutions of higher learning. The subjects were 238 private colleges throughout Malaysia. This study adopted the Dimensions of the Learning Organization Questionnaire (DLOQ) developed by Watkins and Marsick (1997) to measure the seven learning organization action imperatives, which are necessary to the development of a learning culture. Additionally, two perceived performance improvement measures were also adopted from the DLOQ. Past studies together with this study have proved the validity and reliability of the DLOQ. Six institutional characteristics were employed in this study: age of the institute, number of full-time employees, institutional level of commitment to research productivity, effective teaching and learning, institutional/professional service, and community service. Exploratory model building was used to develop four best models that maximized the perceived changes in financial and knowledge performance in relation to the seven learning organization dimensions and institutional characteristics. It was discovered that there were positive, somewhat high, and significant relationships between the seven dimensions of learning organization and the dependent variables, perceived financial and knowledge performance. Four of the dimensions demonstrated a strong relationship: continuous learning, team learning, embedded systems and providing leadership. The institutional characteristics that jointly affecting the private colleges performance were perceived level of institutional commitment to institutional/professional service and institutional level of commitment to effective teaching and learning. The findings of this study will facilitate human resource development practitioners by providing empirical information, which supports the concept of the learning organization and their positive influence on the financial and knowledge performance, particularly in the private higher education industry. Moreover, this study would fill the vacuum in the body of knowledge concerning the learning organization dimensions, institutional characteristics and performance improvement.